Junk-food consumption and bodyweight management among junior secondary school students in Obio/Akpor LGA of Rivers State, Nigeria - Eze, Precious; Bamson, Minaseichinbo (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study investigated how the regular consumption of junk food affects body weight management among junior secondary school students in Obio/Akpor Local Government Area (LGA) of Rivers State. It employed a correlational research design with a sample size of 385 Junior Secondary Class 3 students. Five public secondary schools were randomly selected from Obio/Akpor LGA, and students were chosen for the study using proportional stratified random sampling through balloting. Data was collected using a 46-item validated instrument called the Junk-food Intake and Awareness Questionnaire (JIAQ), which measured junk food awareness level, frequency of junk food consumption, body weight management strategies, and participants' ages. Additionally, the weight and height of the respondents were measured. The reliability of JIAQ was assessed using the Cronbach formula, yielding a coefficient of 0.89. Descriptive and inferential statistics, including frequency, percentages, mean, standard deviation, and regression analysis, were employed for data analysis. The findings revealed that junior secondary school students had an above-average awareness of junk food, with frequent consumption of items such as burgers, spring rolls, and egg rolls. Body weight management practices among the students were slightly above average. The study found a strong, inverse, and significant relationship between junk food awareness and body weight, as well as a strong, positive, and significant relationship between the frequency of junk food consumption and body weight among junior secondary students in Obio/Akpor LGA of Rivers State. Recommendations included raising students' awareness of junk food available in eateries and restaurants in the LGA, aiming to reduce the regularity of consumption of such foods. This awareness is likely to contribute to better management of body weight among students.